Sex-Specific Impact of Pain Severity, Insomnia, and Psychosocial Factors on Disability due to Spinal Degenerative Disease. (7th May 2020) - Koh, Keito; Yamada, Keiko; Enomoto, Tatsuya; Kawai, Aiko; Hamaoka, Saeko; Chiba, Satoko; Iseki, Masako
Abstract : Purpose . Pain experience due to spinal degenerative disease decreases activity of daily living and quality of life. The present cross-sectional study was aimed at examining the sex-specific impact of pain severity, psychosocial factors, and insomnia on the disability due to chronic pain arising from spinal degenerative disease. Methods . In total, 111 outpatients with chronic spinal degenerative on initial diagnosis were analyzed. The definition of chronic spinal degenerative disease was (1) pain duration ≥3 months, (2) findings of nerve root compression on neurological examination and imaging, and (3) localized neck or lower back pain (not widespread, upper or lower limb pain). We used Numerical Rating Scale (NRS), Pain Disability Assessment Scale (PDAS), Hospital Anxiety and Depression Scale (HADS), Pain Catastrophizing Scale (PCS), and Athens Insomnia Scale (AIS) to assess patients. Univariate regression analysis was performed to investigate whether sex influences the PDAS score, and sex-stratified multivariate regression analysis was conducted to identify the variables associated with the PDAS score. Results . Sex was identified as a predictor of the PDAS score (standardized coefficient ( β ) = 0.28; 95% confidence interval (CI), 0.10–0.46; p = 0.003 ). In men, the AIS score was associated with PDAS ( β  = 0.36, 95% CI 0.09–0.63). Age ( β  = 0.31, 95% CI 0.06–0.55) and NRS ( β  = 0.40, 95% CI 0.14–0.67) were associated with PDAS in women. HADS-A, HADS-D, and PCS were not associated with PDAS in both sexes. Conclusion . Insomnia was associated with disability in men, whereas aging and pain severity were associated with disability in women. Catastrophic thinking was not associated with disability in both sexes.